LED light effect on growth, pigments, and antioxidants of lettuce (Lactuca sativa L.) baby greens - Mousumi Jahan Sumi; Noushin Jahan; Syed Sakib Thamid; Md. Emon Ibne Tarik; Sahar Hassannejad; Mehdi Rahimi; Shahin Imran (BMC Plant Biology)
Abstract Red and green lettuce baby greens provide additional health benefits because they are high in nutrients, pigments, and antioxidants. This study examines red coral lettuce (Lactuca sativa L. var. cripsa) and green lettuce (Lactuca sativa L. var. longifolia) baby greens grown for 20 days in a soil-vermicompost-compost (50:30:20) mixture to determine how different LED light spectra affect their growth, pigment accumulation, and antioxidant qualities. Plant height, biomass, and other growth parameters were evaluated manually, while pigments, phenolics, and flavonoids were analyzed using spectrophotometric techniques. In terms of growth, green lettuce fared better than red lettuce, with a biomass of 5.90 ± 0.35 g/ 100 plant and a plant height of 6.86 ± 0.23 cm, particularly during exposure to red + blue light. Red + blue as well as red light caused a considerable decrease in chlorophyll concentration; under red light, green lettuce's chlorophyll content dropped by up to 59.61%. Both species' phenolic (100%) and flavonoid (100%) contents were increased by white light, but red light produced the lowest levels. Blue light maintained the highest levels of carotenoid concentration while all other treatments saw a decline. With white light maximizing antioxidant content and red + blue light encouraging growth, principal component analysis (PCA) analysis demonstrated the substantial impact of light treatments on pigment and biochemical composition. Overall, the study concludes that treatments with LED light have a significant impact on red and green lettuce baby greens’ development, pigment buildup, and antioxidant qualities.